The activity profile in international taekwondo competition is modulated by weight category - Bridge, C. A.; Jones, M. A.; Drust, B. (International Journal of Sports Physiology and Performance, 2011)
Purpose: To examine the activity profiles of elite male competitors during international Taekwondo competition in relation to fin, feather, and heavy weight categories. Methods: Twelve male Taekwondo competitors equally representing fin, feather, and heavy weight divisions were studied during the 2005 World Taekwondo Championships using a time-motion system developed to analyze the activities and activity phases. The frequency and duration of activities were recorded and assimilated into four independent activity phases: fighting activity, preparatory activity, nonpreparatory activity and stoppage activity. The total number of exchanges and kicks were also calculated for each combat. Results: For all weight groupings the mean ± SD fighting time was 1.7 ± 0.3 s, preparatory time 6.4 ± 2.1 s, nonpreparatory time 3.0 ± 0.6 s, referee stoppage time 2.8 ± 0.9 s and 28 ± 6 exchanges and 31 ± 7 kicks were performed. Differences in the mean fighting time (fin: 1.4 ± 0.2 s vs heavy: 1.8 ± 0.3 s; P = .03; effect size [ES] = 1.57), preparatory time (fin: 5.3 ± 1.0 s vs feather: 8.2 ± 2.6 s; P = .03; ES = 1.47) and the total number of exchanges (feather: 24 ± 6 vs heavy: 32 ± 5; P = .03; ES = 1.44) were identified between the weight categories. Conclusion: The activity profile in international Taekwondo competition was modulated by competitors` weight category. These findings suggest that conditioning sessions may need to be specialized to the requirements of specific weight categories.